Hydrogen and steam injected tandem μ-reactor GC/FID system: phenol recovery from bisphenol A and alkylphenols using Ni/Y zeolite. Issue 12 (10th October 2019) - Kumagai, S.; Asakawa, M.; Kameda, T.; Saito, Y.; Watanabe, A.; Watanabe, C.; Teramae, N.; Yoshioka, T.
Abstract : Hydrogen and steam injected tandem μ-reactor-GC/FID system achieved online quantification of products from hydrogenation and dealkylation of bisphenol A and alkylphenols using Ni/Y zeolite. Abstract : A tandem μ-reactor-gas chromatograph/flame ionisation detector (TR-GC/FID) system that allows hydrogen and steam injection, called H2 /steam-TR-GC/FID, was newly developed to quantitatively evaluate phenol recovery from the pyrolysis of bisphenol A (BPA), isopropyl phenol (iPrP), and isopropenyl phenol (IPP). Ni-Loaded Y-zeolite (Ni/Y) was selected to simultaneously catalyse BPA decomposition into phenol and IPP, IPP hydrogenation to iPrP, and iPrP dealkylation to phenol and propylene. These substrates were evaporated in the 1st μ-reactor, and then converted into phenol using Ni/Y-zeolite under H2 /steam flow in the 2nd μ-reactor. The products were directly introduced into GC/FID and quantified using naphthalene as the internal standard. Although the steam injection caused degradation of product peaks, this drawback was overcome by using two-step ice- and cryo-traps. The phenol yield was negligible when the three substrates were pyrolysed alone at 350 °C, but became substantially enhanced by the combination of H2, steam, and Ni/Y, reaching the maximum of 89%, 46%, and 62% from iPrP, IPP, and BPA, respectively. Hence, these results indicate the possibility to obtain phenol-rich products from the pyrolysis of polymeric wastes with BPA macro skeleton. In addition, the developed high-throughput analytical technique can accelerate the development of other gas–solid reaction systems under H2 /steam atmosphere.